Effects of Different Periods on Bilateral Relationship of Urdu Travelogues and Mythos - Khalid, Anaa; Salman Bhatti, Muhammad (sourcecoder, 2022)
Travelogues are considered as the most important pillar of knowledge in Urdu literature. In the past, it has been reported that it is used for a source of information about society only. With the passage of time it has been completely developed as singular branch. Recently, tones of travelogue writings are become the part of Urdu literature. Travelers visited countries of their interest and jotted downs their feelings, observations, countries’ social and economic situation, politics, history, their religions and education system and many mores. Many travelogues were written in the form of short stories but there’s a minute difference in between them. This article describes the bilateral relationship of travelogues and mythos (short stories) in different centuries. The well-known travelogue writers; Mustansar Hussain Tarar, Raza Ali Abdi, Sadut Hassan Manto, Ahmed Nadeem Qasmi, Qudrat Ullah Shahaab, Bano Qudsia, Hajra Masror and Azeez Ahmed are significantly discussed.